The effect of modified observation-teaching-discussion pedagogy combined with microteaching on the critical thinking ability of nursing interns in China: a quasi-experimental study - Wu, Sheng-Mei; Lei, Yan-Yuan; Miao, Qing; Wang, Jia-Qin; Tian, Yu-Feng; Xi, Zu-Yang (Frontiers in Education, 2023)
Aim The aim of this study is to investigate the effect of modified observation-teaching-discussion pedagogy combined with microteaching on improving the critical thinking ability of nursing interns in China. Methods Two hundred baccalaureate nursing students practicing in the department of neurosurgery were divided into two groups chronologically, with 100 students per group. The control group received traditional clinical mentoring while their counterparts in the intervention group received mentoring by modified observation teaching discussion pedagogy combined with microteaching. Then, we compared the two groups with respect to theoretical knowledge and nursing operation skills. The Critical Thinking Ability Scale was used to evaluate the critical thinking ability of the two groups of nursing students. Data were analyzed with SPSS 22.0 software. Results Following the internship, the scores of nurses in the intervention group were significantly higher than those in the control group for theoretical knowledge, technical skills and critical thinking ability (p < 0.05 for all). Conclusion The application of modified observation-teaching-discussion pedagogy in combination with microteaching promoted the knowledge, technical skills and critical thinking ability of nursing students in clinical practice.